Digital transformation, financial access and discrepancies in household wealth accumulation - Koffi Sodokin; Joseph Kokouvi Djafon; Mawuli Couchoro; Akoété Ega Agbodji (Cogent Economics & Finance, 2023)
In a world where financial capital serves as the backbone of individual and societal economic health, understanding the mechanisms that can stimulate or hinder its accumulation is critical. This study explores how the accessibility of banking services and the integration of digital finance can influence the accumulation of financial wealth, as well as disparities in household savings. Drawing on data derived from the Finscope Consumer Survey for Togo 2016 and the Harmonized Living Standards Measurement Study 2018 for Togo, this study employs a range of analytical methodologies including propensity score matching, double difference, and smoothed instrumental variable quantile regression tools. The outcomes of this study underscore that access to banking services and digital finance significantly enhances physical asset investment and the adoption of sound financial practices rather than an increase in bank savings alone. Therefore, the emergence of digital finance can be seen as a missing link in the formal financial system's ability to improve the efficiency of financial service provision and make a significant contribution to reducing inequalities in wealth accumulation. This study sheds light on the significant decrease in inequality concerning the capacity for wealth accumulation among households.
Keywords: G21; O33; O41; O55; 330; bank financial services access; digital finance; wealth accumulation